Drainage Patterns to Nontraditional Nodal Regions and Level IIB in Cutaneous Head and Neck Malignancy. (3rd October 2016) - Creighton, Francis; Bergmark, Regan; Emerick, Kevin
Abstract : Objectives: (1) Determine the frequency of nontraditional sentinel lymph node (SLN) locations in cutaneous head and neck malignancy and (2) determine the frequency of level IIB SLNs in cutaneous head and neck malignancy. Design: Case series with chart review. Setting: Tertiary academic hospital. Subjects and Methods: In total, 145 consecutive sentinel lymph node biopsy (SLNB) specimens for cutaneous head and neck malignancies were reviewed from 2007 to 2015. Nodal regions were categorized into levels I to V, parotid, external jugular (EJ), perifacial, suboccipital, and postauricular regions. Primary locations were divided into scalp, forehead, cheek, ear, neck, nose, periocular, and lip. Frequencies of sentinel lymph node (SLN) locations for each primary location were determined. Results: Parotid, EJ, perifacial, suboccipital, postauricular, and level IIB lymph SLNs were identified as nontraditional lymph node regions at risk in head and neck cutaneous malignancy. EJ SLNs were present in over 15% of all cases and over 25% of periocular and cheek lesions. Perifacial SLNs were frequently present in nose and lip lesions. Suboccipital and postauricular nodes were only present in scalp lesions. Level II was the most common location for a SLN. In total, 15.9% of all cases involved level IIB. Scalp and ear primary lesions were most likely to drain to level IIB. Conclusions: Nontraditional SLN locations, such as EJ, perifacial, suboccipital, postauricular, and parotid, as well as level IIB, are important sites of drainage for head and neck cutaneous malignancy. Prediction of at‐risk lymph node regions is important to help guide SLNBs, elective and completion neck lymphadenectomy and radiation, and long‐term observation.